Exploring the Potentials of Microlearning in English Language Teaching in Higher Education - Barus, Irma Rasita Gloria; Bontisesari (Asian Journal of Applied Education (AJAE), 2023)
Recent trends in language education have demonstrated the dynamic use of technology in accommodating the needs of today’s learners. In relevance to the characteristics of digital natives, there is an urgency to transform teaching and learning practice. One promising approach to this matter is microlearning. Hence, this article aims to conduct a scoping review on the potential of microlearning in English language teaching. By examining twenty published research articles, this study sets two foci: how microlearning is used in digital platforms and how microlearning is addressed in ELT for higher education. This study reveals that microlearning approach is worth exploring to be applied in language pedagogical practices and to accommodate the 21st century English language learners in a post-pandemic context.